Fatores determinantes do desempenho de jovens nadadores em provas de 100 e 400 metros de nado livre - Seffrin Neto, Aldo Antonio [UNIFESP] (2019)
Swimming is a very popular sport especially amongst young people. It is known that swimming performance is influenced by several factors, such as anthropometric and physiological aspects. However, the level of relative contributions of these variables to swimming performance in different age groups is not clear. Therefore, the aim of the present study was to analyze the characteristics of aerobic endurance, anthropometry and neuromuscular fitness to fit a multiple regression model to verify which factors better explain performance in 100- and 400-meter freestyle swimming events in each age group. Sixty swimmers from both sexes participated in the study (13.80 ± 2.61 years old, 1.62 ± 0.10 m, 52.36 ± 12.01 kg). They were divided into three groups: 11 to 12 years old (G1), 13 to 14 years old (G2) and 15 to 23 years old (G3), further subdivided by sex. Initially, the relationships were analyzed by dispersion diagrams and Pearson's linear correlation coefficients. Then, Stepwise multiple regression models were fitted to determine the relationships between anthropometric variables, critical velocity, handgrip strength, vertical jumping power and height, muscle torque and power of knee flexor and extensor muscles and internal and external rotators of the shoulders, age, sex and biological maturation. Results show that the parameters independently contribute to the stepwise prediction model of performance and that the models differ between the three age groups. Critical velocity is an important variable in both events for all age categories. Both lean mass and muscular power were performance determinants for G2 & G3 and muscular strength for G3. The understanding of these variables can contribute to the development of proper training programs for each age group, identify athletic talents and direct athletes to the events for which they have a more adequate physical and physiological profile.